PENGARUH PENGGUNAAN MEDIA BELAJAR QUIET BOOK TERHADAP PEMAHAMAN PENDIDIKAN SEKSUAL BAGI ANAK TUNAGRAHITA DI HOMESCHOOLING KAK SETO - Jannata Firdausy, Biha; Mulia, Dedi; Maslahah, Sayidatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of using quiet book learning media on the understanding of sexual education among children with intellectual disabilities at Kak Seto Homeschooling. The subject was one student with intellectual disabilities in Grade IV of an inclusive elementary school at Kak Seto Homeschooling, South Tangerang, identified by initial H (age 10). The study employed Single Subject Research (SSR) method with an A-B-A design. Data were collected through a validated sexual education comprehension test. The results showed an increase in mean levels from baseline-1 (A1) at 33%, intervention phase (B) at 88.5%, and baseline-2 (A2) at 70%. The overlap percentage from A1 to B and B to A2 was 0%, indicating that the intervention had a significant effect. Therefore, the use of quiet book learning media has been proven to positively affect the sexual education understanding of children with intellectual disabilities.